Konstruksi Pendidikan Islam Moderat Melalui Nalar “A Common Word” Waleed El-Ansary - Fahmi, Muhammad; Saefullah Azhari; Syaifuddin; Muhammad Fladimir Herlambang (State Islamic Institute of Madura, 2021)
This paper seeks to understand the construction of moderate Islamic education in Waleed El-Ansary's